2019
DOI: 10.1101/699934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

tRNA 2’-O-methylation modulates small RNA silencing and life span in Drosophila

Abstract: 2'-O-methylation (Nm) represents one of the most common RNA modifications. Nm affects RNA structure and function with crucial roles in various RNA-mediated processes ranging from RNA silencing, translation, self versus non-self recognition to viral defense mechanisms. Here, we identify two novel Nm methyltransferases (Nm-MTases) in Drosophila melanogaster (CG7009 and CG5220) as functional orthologs of yeast TRM7 and human FTSJ1, respectively. Genetic knockout studies together with MALDI-TOF mass spectrometry a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 93 publications
(151 reference statements)
1
9
0
Order By: Relevance
“…RNA was extracted from Drosophila ovaries following standard methods detailed in (Molla-Herman et al, 2015;M. Angelova, 2019).…”
Section: Rna Extraction From Ovariesmentioning
confidence: 99%
See 4 more Smart Citations
“…RNA was extracted from Drosophila ovaries following standard methods detailed in (Molla-Herman et al, 2015;M. Angelova, 2019).…”
Section: Rna Extraction From Ovariesmentioning
confidence: 99%
“…In Drosophila it has been recently shown that methylation marks protect tRNAs from cleavage and aberrant tRFs populations accumulate in mutants: on the one hand, Dnmt2 mutation impairs m 5 C methylation (Schaefer et al, 2014;Genenncher et al, 2018) and on the other hand, CG7009 and CG5220 mutation impairs 2'-O-methylation (M. Angelova, 2019). 2'-O-methylation is one of the most common RNA modifications and consists in the addition of a methyl group to the 2' hydroxyl of the ribose moiety of a nucleoside, being also known as Nm.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations